PERAN GURU BIMBINGAN KONSELING DALAM MENINGKATKAN SELF ESTEEM PESERTA DIDIK DI MAN 1 DAN MAN 2 MALUKU TENGAH - Nakir Tomagola Tomagola; Adam Latuconsina Latuconsina; Muhajir Abd Rahman (Jurnal Studi Islam, 2023)
The problem in this study is how the role of counseling guidance teachers in increasing self-esteem of students in MAN 1 and MAN 2 Central Maluku, Central Maluku district. And what are the factors that support and inhibit the role of counseling guidance teachers in increasing  self-esteem of students in MAN 1 and MAN 2 Central Maluku. This type of qualitative descriptive research. This research was conducted from 6 June to 6 July 2022 in MAN 1 and MAN 2 Central Maluku. The informants in MAN 1 consist of 1 BK teacher and 4 students and in MAN 2 there are 1 BK teacher and 4 students. Collecting data through observation, interviews and documentation, analyzed data using data reduction, data assessment and drawing conclusions. The role of BK teachers in increasing self-esteem of students in MAN 1 includes: 1. Build a positive mindset in students, 2. Recognize the weaknesses and strengths of students, 3. Increase the competitive spirit of students, 4. Provide training to students to increase self-esteem, and 5. Ask each student to appear in front of the class, b. Supporting factors include: 1. Factors the role of teachers and homeroom teachers), 2. Cooperation with parents of students, 3. BK room facilities and infrastructure, 4. Support from the school and the school environment, and 5 Personality of guidance and counseling teacher,c. Inhibiting factors, including: 1. Internal factors (from students), 2). External factors (association in the community). Meanwhile, the role of BK teachers in increasing and self-esteem of students at MAN 2 Maluku includes; 1. Directing students to do good, 2. Look for the uniqueness (weaknesses and strengths) of students to be used as examples, 3. Creating student competition, 4. Train students, b. Supporting factors include; 1. School element factors, 2. Parental cooperation, 3. BK room facilities, 4. The authority of the BK teacher, c. Inhibiting factors: 1. Internal factors from students and 2. External factors, community environment.Tujuan penelitian untuk mendeskripsikan dan menganalisis peran guru bimbingan konseling dalam meningkatkan self esteem peserta didik di MAN 1 dan MAN 2 Maluku Tengah dan menguraikan faktor pendukung dan penghambat peran guru bimbingan konseling dalam meningkatkan self esteem peserta didik di MAN 1 dan MAN 2 Maluku Tengah. Tipe penelitian deskriptif kualitatif, Informan di MAN 1terdiri dari 1 orang guru BK dan 4 orang peserta didik dan di MAN 2 terdiri dari 1 orang guru BK dan 4 peserta didik. Pengumpulan data melalui observasi, wawancara dan dokumentasi, analisis data menggunakan reduksi data, pengkajian data dan penarikan kesimpulan. Hasil penelitian, yaitu peran guru BK dalam meningkatkan self esteem terdiri dari 1. Membangun pola pikir positif pada peserta didik, 2. Mengenali kekurangan dan kelebihan peserta didik, 3.Meningkatkan semangat kompetitif peserta didik, 4. Memberikan pelatihan meningkatkan rasa harga diri, dan 5) Meminta setiap peserta didik tampil di depan kelas b. Faktor pendukung : 1) Peran guru dan wali kelas, 2) Kerjasama dengan orang tua, 3) Sarana dan prasana ruang BK, 4) Dukungan pihak sekolah dan lingkungan, dan 5) Kepribadian guru bimbingan dan konseling, c. Faktor penghambat: 1. Faktor internal peserta didik, 2). Faktor eksternal: pergaulan di lingkungan masyarakat. Sedangkan peran guru BK dalam meningkatkan self esteem peserta didik di MAN 2 Maluku Tengah meliputi; 1) Mengarahkan siswa untuk berbuat baik, 2) Mencari keunikan (kekurangan dan kelebihan) siswa untuk dicontoh, 3) Menciptakan persaingan siswa, 4) Melatih siswa, b. Faktor pendukung; 1. Faktor elemen sekolah, 2. Kerjasama orang tua, 3. Fasilitas ruang BK, 4. Kewibawaan guru BK, c. Faktor penghambat: 1. Faktor internal dari peserta didik dan 2. Faktor eksternal: lingkungan masyarakat.